Ankle joint rotation and exerted moment during plantarflexion dependents on measuring- and fixation method. - Savvas Stafilidis (Public Library of Science (PLoS), 2021)
We examined the effect of ankle joint fixation vs increased foot pressure (aiming to reduce dynamometer-subject elasticity (DSE)) on the exerted moment during plantarflexion contraction. We also examined the joint rotation in dependence of the measuring site (forefoot, rearfoot) and the foot condition (fixed, free). We hypothesized higher exerted moments due to reduced DSE compared to fixed condition and an effect of fixation on the joint rotation in dependence of the measuring site. Fourteen healthy individuals (28.7±6.9y) completed in randomized order maximal isometric plantarflexions in four different positions (0-3-6-9 cm) and two ankle joint conditions (fixed-free). Kinematics of the rear- and forefoot were obtained synchronously. We found higher moment in the fixed compared to the free condition at all positions. The maximum moment in the fixed condition did not differ at any position. At the fixed condition, the forefoot rotation did not differ at any position (~5°) while at free condition we observed a significant rotation reduction (form ~12 to ~5°). The rearfoot rotation did not differ between conditions at any position while a significant joint angle reduction was observed (~10 to ~6° and ~12 to ~6°; fixed-free respectively). The results indicate that with appropriate foot fixation the maximum moment can be achieved irrespective of the position. With the foot secured, the measuring site influences the rotational outcome. We suggest that for a minimization of the joint rotation a fixation and the forefoot-measuring site should be preferred. Additionally, for unconstrained foot kinematic observations both measuring sites can be obtained.